Microstructure and mechanical properties of powder metallurgy Ti–22Al–24Nb–0.5Mo (at.%) alloys. (November 2015) - Wu, J.; Xu, L.; Guo, R. P.; Lu, Z. G.; Cui, Y. Y.; Yang, R.
Abstract : The Ti–22Al–24Nb–0.5Mo (atomic fraction, %) pre-alloyed powder was produced by gas atomisation. Powder metallurgy Ti2 AlNb alloys were prepared by a hot isostatic pressing procedure. The influence of experimental variables including hipping temperatures, solution and aging temperatures on microstructure and properties of powder metallurgy Ti2 AlNb alloys was assessed. The experimental results showed that hipping temperature affected the porosity distribution and mechanical properties of powder metallurgy Ti2 AlNb alloys. Good comprehensive mechanical properties (tensile strength, ductility and rupture lifetime) could be obtained through an optimised heat treatment process.